Presence of Candida and its associated factors in participants attending oral cancer screening in the lower northeastern area of Thailand - Krongkan Deeiam; Jintana Pankam; Vanvisa Sresumatchai; Patama Visedketkan; Warut Jindavech; Dulyapong Rungraungrayabkul; Kununya Pimolbutr; Boworn Klongnoi; Siribang-on Piboonniyom Khovidhunkit (BMC, 2023)
Abstract Background Certain evidence indicated high prevalence of Candida in oral potentially malignant disorders (OPMDs) and oral cancer (OC). This study was aimed to investigate the presence of Candida and its associated factors in participants who attended the oral cancer screening program in the lower northeastern districts of Thailand. Methods Convenient participants residing in the lower northeastern districts of Thailand who attended the oral cancer screening were enrolled. A questionnaire retrieving demographic characteristics, risk factors of oral cancer, and risk of having Candida was completed. Oral examination was performed by oral medicine specialists or oral surgeons. The participants were categorized into 4 groups according to their clinical diagnosis, namely normal oral mucosa (NOM), OPMDs/OC, non-OPMDs/OC and clinically suspected oral candidiasis (CSOC). Stimulated saliva flow rate was measured. Dip-slide test was performed in each participant to evaluate the presence of Candida. The levels of Candida were categorized into high and low levels according to the score received from the dip-slide test. Factors associated with high levels of Candida were identified using multivariate logistic regression analysis. Results A total of 577 participants were recruited. High levels of Candida were found in 31.3%, 24.7%, 25.9% and 18.1% in the OPMDs/OC, the non-OPMDs/OC, the CSOC and the NOM groups, respectively. According to multivariate logistic regression analysis, age above 60 years, female gender, betel quid chewing habit, use of denture, hyposalivation, and being in the CSOC group were found to be significantly associated with high levels of Candida. Conclusion Higher number of participants in the OPMDs/OC group was found to have high levels of Candida. Increasing age, female gender, betel quid chewing habit, use of denture, hyposalivation and having CSOC lesions were associated with high levels of Candida.